2010
DOI: 10.1210/jc.2009-2596
|View full text |Cite
|
Sign up to set email alerts
|

Human Chorionic Gonadotropin Up-Regulates Expression of Myeloid Cell Leukemia-1 Protein in Human Granulosa-Lutein Cells: Implication of Corpus Luteum Rescue and Ovarian Hyperstimulation Syndrome

Abstract: We first demonstrate that hCG prevents apoptosis of granulosa-lutein cells through the induction of Mcl-1 protein via the LH/hCG receptor and a cAMP response element-binding protein-dependent pathway. We may have found the molecular mechanism for luteal rescue during early pregnancy. Mcl-1 prevents apoptosis and increases cell viability but not proliferation as mechanisms for luteal rescue. Mcl-1 is a key molecule of hCG signaling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 45 publications
3
10
0
1
Order By: Relevance
“…This suggests putrescine‐induced reactivation of luteal activity may be mediated through increased cell survival and thus preventing luteal cells from undergoing apoptosis. As it is well demonstrated that LH through its receptor (LH/hCG‐receptor) protects luteal cells from undergoing apoptosis during early pregnancy (Chen et al, ) and similarly in this study treatment with putrescine upregulated LHR, it is likely that putrescine via LHR contributes to reactivation of luteal activity by promoting cell survival and suppressing apoptosis.…”
Section: Discussionsupporting
confidence: 74%
“…This suggests putrescine‐induced reactivation of luteal activity may be mediated through increased cell survival and thus preventing luteal cells from undergoing apoptosis. As it is well demonstrated that LH through its receptor (LH/hCG‐receptor) protects luteal cells from undergoing apoptosis during early pregnancy (Chen et al, ) and similarly in this study treatment with putrescine upregulated LHR, it is likely that putrescine via LHR contributes to reactivation of luteal activity by promoting cell survival and suppressing apoptosis.…”
Section: Discussionsupporting
confidence: 74%
“…Following a decline in LH support, hCG is the foremost leutotropic paracrine signal produced by the embryo, well before the implantation begins [7]. This hCG signaling critically influences the blastocyst development, uterine receptivity through stromal fibroblast proliferation, secretion of IGF binding protein-1, NK cell activation and apoptosis (Fas-FasL), transient immune tolerance through activation of regulatory T-cells and dendritic cells (MHC class II, IL-10 and IDO expression), and endometrial angiogenesis through secretion of VEGF [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…One of the important aspects of the female reproductive cycle is that ovulation is controlled by a pulsatile secretion of LH (LH surge) that is subject to individual variation [3]. In controlled ovarian stimulation (COS), this variability of ovarian activities is temporarily eliminated by GnRH agonists/antagonists, while at the same time the ovarian functions are regulated by exogenously injected FSH and LH/hCG [4-7]. …”
Section: Introductionmentioning
confidence: 99%
“…The potential role of the VEGF/VEGF-receptor (VEGF-R1 and R2) system in the appearance of OHSS is based on certain evidence: a) it has been demonstrated that VEGF increases the vascular permeability of endothelial cells, which could lead to a shift in fluids from the blood vessels to the third space (26-28); b) vascular permeability increased after hCG during ovarian stimulation; c) the occurrence of OHSS is strongly correlated with the application of hCG during ovarian stimulation, leading to an increased VEGF expression by granulosa cells from corpora lutea (29-31) d) In OHSS patients, the amount of VEGF in the follicular fluid is frequently higher than in persons not affected by this complication (32), thus also proving the ovarian origin of VEGF; e) the VEGF-R2 expression increases at the same time that the vascular permeability peaks, demonstrating that the VEGF-VEGF receptor system is implicated in OHSS (27, 28). …”
Section: Phisiopathologymentioning
confidence: 99%